Ultrasonic evaluation of the ocular axia following orthokeratology - Xia Jiang (Guoji Yanke Zazhi, 2014)
AIM: To discuss the change of anterior chamber depth(ACD), lens thickness(LT)and axial length(AL)for following orthokeratology. METHODS:Orthokeratology was performed for 120 patients(120 eyes), and conducted a prospective clinical study. The ultrasound examination results were compared before and after 1a of orthokeratology. RESULTS: The LT value increased by 0.14mm in the group of low and moderate myopia(P<0.01)and 0.05mm in the group of moderate and high myopia, indicating a statistically significant difference. No significant difference was found in ACD value and AL value following orthokeratology(P>0.05). CONCLUSION: Crystalline lens power is changed following orthokeratology. Accommodation factor may be the possible mode of action of orthokeratology in reducing myopic progression.